Smart city communication via social media: Analysing residents’ and visitors’ engagement. - Molinillo-Jiménez, Sebastián; Anaya-Sánchez, Rafael; Morrison, Alastair M.; Coca-Stefaniak, Andres (My University, 2019)
This research applies a unique conceptual model and methodology incorporating popularity, commitment, and virality to measure the social media engagement with residents and visitors of smart cities and how they communicate ‘smart’ elements and their brands. Digital content analysis was applied to a sample of ten Spanish smart cities (including Barcelona, Bilbao, Madrid, Seville and Valencia, among others), with measurable and quantifiable elements of engagement (e.g., likes, shares and comments). The smart cities analysed achieved acceptable, but rudimentary, levels of engagement via social media using Facebook, Twitter and Instagram. However, they displayed weaknesses related to their image and branding as well as the effectiveness with which they communicated their smart characteristics. The main implication of this research is that these Spanish smart cities have considerable scope to improve their use of social media to enhance their communications and branding. Greater emphasis is required on delivering emotional (affective) messages and a higher priority needs to be given to business and business event travellers and those visiting friends and relatives.
Keywords: Redes sociales en Internet; Ciudades - Marketing; Smart cities; Social media; Engagement; City branding; User-generated content (UGC)